Pengungkapan Corporate Social Responsibility dan Likuiditas Dalam Meningkatkan Kinerja Keuangan - Wulansari, Retna Ayu; Dasuki, Tito Marta Sugema (Papanda Publisher, 2024)
The capital market has become an alternative funding avenue supporting companies in expanding their operational scale and enhancing profitability. The evolving financial position has become pivotal in assessing a company's performance. Financial reports serve as tools to evaluate a company's financial health, playing a crucial role in decision-making and reflecting the company's performance. Financial performance factors encompass efficiency, technological advancements, and distribution balance. Corporate Social Responsibility (CSR) disclosure and liquidity are primary considerations in assessing financial performance. This research employs an explanatory survey approach and descriptive-verification analysis. The sample involves manufacturing companies listed on the Indonesia Stock Exchange between 2012-2014. Secondary data collection methods involve content analysis of the companies' annual reports. Descriptive statistical analysis, correlation, multiple linear regression, and F and t-tests are utilized to analyze the data. Descriptive data show that the CSR variable has an average disclosure of 0.2667, average liquidity of 2.0895, and average financial performance of 0.2034. Correlation reveals that CSR has a moderate positive relationship with financial performance (0.444), while liquidity exhibits a moderately stronger positive relationship with financial performance (0.502). CSR contributes 19.71% to financial performance, whereas liquidity contributes 25.20%. Multiple linear regression analysis indicates that both independent factors, CSR and liquidity, significantly influence financial performance positively. Findings illustrate that CSR disclosure and liquidity hold a significant positive relationship with financial performance. CSR contributes 19.71% to financial performance, while liquidity contributes 25.20%. These results indicate the importance of CSR and liquidity as factors influencing the financial performance of manufacturing companies on the Indonesia Stock Exchange.